Clinical Comparison of Two Self-Directed Bleaching Systems - Katherine Karpinia, DMD, MS,1 Ingvar Magnusson, DDS Odont Dr,2 (Journal of Prosthodontics, 2003)
This randomized clinical trial compared the clinical efficacy and tolerability of 2 marketed self-directed vital tooth-whitening systems.